+0  
 
0
48
3
avatar

I don’t understand this stuff

 

 Sep 16, 2020
 #1
avatar+326 
0

set the equation to  6x+x=16x-4. find x, and plug it in for the 16x-4 to find FH.

 

:)

 Sep 16, 2020
 #2
avatar
0

G is midpoint of FH, which means:

 

FG = GH. But FG =6x. So:

 

6x + 6x = FH. But FH = 16x - 4. So:

 

6x +6x =16x - 4

 

12x = 16x - 4

 

16x - 12x = 4

 

4x = 4   and x = 1. And:

 

FH =16x - 4 = 16*1 - 4 

 

FH = 12

 Sep 16, 2020
 #3
avatar+198 
0

16x - 4 = 2*6x

 

16x - 4 = 12x

 

4x = 4

 

x = 1

 

FH = 2*6x = 12

 Sep 16, 2020

57 Online Users

avatar